Un enfoque desde la ingeniería de software a una solución tecnológica de IoT y aprendizaje automático que permita monitorear y controlar las variables medioambientales en un cultivo de café - Ruiz Martinez, William; González Gómez, Arnaldo Andrés (Ingeniería, 2022)
Context: Software engineering allows us to approach software design and development from the practical application of scientific knowledge. In the case of this IoT solution and the machine learning approach to the monitoring and control of environmental variables in a coffee crop, it allows us to visualize certain artifacts of the system in their interaction with users and their behavior with other artifacts or devices that constitute a technological solution. Method: For this work, the application of software engineering from a conceptual approach and the behavior of the system is proposed. To meet these objectives, we decided to use the Unified Modeling Language (UML) in such a way that the most important components of the technological solution could be represented from a static perspective through the use case diagrams, as well as from a dynamic viewpoint through the sequence diagrams. Results: Through the application of the UML, it was possible to develop the conceptual and behavioral modeling of certain artifacts and components. This knowledge allowed identifying the interaction between physical components and devices (machine to machine) and human-machine interaction, that is, the relationship between users and the processes that make up the technological solution. Conclusions: Through software engineering, and more specifically the UML, we were able to establish the importance of knowing the different software artifacts that make up a system or application from a different technical and functional approach, while being able to collect valuable information about the behavior of certain system artifacts, as well as the interaction between users and processes.